Phonon resonant effect in silicon membranes with different crystallographic orientations. (February 2022) - Li, Keqiang; Cheng, Yajuan; Wang, Hongying; Guo, Yangyu; Zhang, Zhongwei; Bescond, Marc; Nomura, Massahiro; Volz, Sebastian; Zhang, Xiaohong; Xiong, Shiyun
Highlights: The phonon resonant strength is strongly dependent on surface orientations of the base membranes. The introduction of resonant pillars can effectively break the ballistic transport characteristics at low-frequencies. Vacancy defects between the pillars and the base material lead to the abnormal increase of thermal conductivity in the resonant structures. the thermal transport at intermediate frequency range is enhanced by the interface vacancy defects. Abstract: Engineering low-frequency phonon transport in nanostructures with the phonon resonant mechanism has become an important research direction. On the basis of non-equilibrium molecular dynamics simulations, the thermal transport in pristine and resonant Si-membranes bounded with {100}, {110} and {111} facets is investigated. It is found that the creation of surfaces can introduce anisotropic thermal transport due to the lattice symmetry breaking. Besides, ballistic phonon transport is found in pristine membranes with lengths up to  500 nm at low-frequencies with a critical frequency mainly dependent on the crystallographic orientation. Moreover, although surface resonances can dramatically reduce the thermal conductivity of all membranes, the resonant effect strongly relies on membrane orientation. Among the three studied membrane orientations, the resonant effect is maximized in the {111}-membrane, where the thermal conductivity is tuned from the largest one to the smallest one among the three membrane types by resonant pillars. The large thermal conductivity reduction in the {111}-membranes by resonances originated from the reduced spectral heat flux between 3 and 12 THz. Furthermore, the resonant coupling strength can be tuned by the interface vacancy between resonant pillars and the base material, which can enhance phonon transport at an intermediate frequency range. Our work provides further insights on thermal transport engineering by phonon resonances and could be useful for thermal conductivity engineering with surface orientations and resonances.